2020
DOI: 10.1002/srin.202000117
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Calcium Aluminate Inclusions by Cerium Treatment in Al‐Killed Steel during Ruhrstahl–Heraeus Refining Process

Abstract: The effect of cerium addition during Ruhrstahl–Heraeus (RH) refining process on liquid calcium aluminum inclusion in Al‐killed steel is studied based on plant trials and thermodynamic calculation. Before cerium addition, liquid calcium aluminum inclusion surrounded by an outer CaS layer are observed. Cerium modified liquid calcium aluminum inclusion to CeAlO3 + CaS + CaO–Al2O3 complex inclusion. The modification process of liquid calcium aluminum inclusion by cerium is different from that of solid Al2O3 or MgO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The addition of La and Ce led to high losses in both cases, the industrial and the laboratory trials. In the industrial experiment, the amount of REEs was approximately 40 ppm, similar to the studies of Gao et al [17] and Geng et al [18] where Ce was used as a tracer. The amount was significantly lower compared to the laboratory trials since the previous investigation of Tian et al [22] found that REEs may increase the clogging tendency.…”
Section: Recovery Ratessupporting
confidence: 78%
See 1 more Smart Citation
“…The addition of La and Ce led to high losses in both cases, the industrial and the laboratory trials. In the industrial experiment, the amount of REEs was approximately 40 ppm, similar to the studies of Gao et al [17] and Geng et al [18] where Ce was used as a tracer. The amount was significantly lower compared to the laboratory trials since the previous investigation of Tian et al [22] found that REEs may increase the clogging tendency.…”
Section: Recovery Ratessupporting
confidence: 78%
“…The employed amount was adopted from other industrial trials documented in the literature. [15,17,18] A compromise was sought to achieve the highest possible REE content within the steel without negatively impacting the castability. Subsequently, another circulation period of 8 min ensured proper homogenization of La or Ce within the melt and promoted inclusion removal, thereby ensuring a high level of cleanness.…”
Section: Industrial Trialmentioning
confidence: 99%
“…With the addition of 80 kg of Ce–Fe alloy, the Ce content of the slabs was increased to 0.0023%. Compared to the sample without adding Ce, the total oxygen and sulphur contents after adding Ce did not be reduced obviously, which has been analysed in a previous study [15].…”
Section: Resultsmentioning
confidence: 78%
“…Related first-order interaction parameters used in this calculation have been listed in Table 3. [27,29,30] The change in Gibbs free energy during the chemical reactions to form rare earth inclusions (the ratio of Ce to La in the alloy was 1:3) at 1600°C according to the reactions and activity coefficients of each element is shown in Figure 6 The formation of rare earth inclusions is related to the Gibbs free energy and affected by mutual transformation. Therefore, the mutual transformation between the rare earth inclusions was further calculated, as shown in Table 4.…”
Section: Thermodynamic Calculation Of Rare Earth Inclusion Formationmentioning
confidence: 99%